2018
DOI: 10.1016/j.ncrna.2018.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Non-coding RNA influences in dementia

Abstract: Dementia is a complex clinical syndrome characterised by progressive decline in cognitive function. It usually presents itself as impairment in memory, loss of judgement, abstract thinking and other disturbances that are severe enough to interfere with activities of daily living. It has long been considered as one of the major challenges at present posing an ever-increasing demand on global health and social care systems. Of all the different forms of dementia, Alzheimer's disease (AD) is the most common. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 110 publications
(141 reference statements)
0
20
0
Order By: Relevance
“…Our study showed that the protein level of OXTR was decreased while the mRNA level was unchanged, suggesting a potential post-transcriptional mechanism as well. Post-transcriptional regulation refers to the regulation of gene expression after RNA transcription and is one of the characteristics of eukaryotic gene expression [45,46]. Studies have shown that lncRNA may participate in the pathophysiological process of depression and regulate DNA transcription and chromosome remodeling [26,47].…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed that the protein level of OXTR was decreased while the mRNA level was unchanged, suggesting a potential post-transcriptional mechanism as well. Post-transcriptional regulation refers to the regulation of gene expression after RNA transcription and is one of the characteristics of eukaryotic gene expression [45,46]. Studies have shown that lncRNA may participate in the pathophysiological process of depression and regulate DNA transcription and chromosome remodeling [26,47].…”
Section: Discussionmentioning
confidence: 99%
“…16,17 We found changes in RNA-modification profiles in the AD brain cortex in both fractions of small RNAs. While the involvement of miRNA in the pathogenesis of AD has been explored 2,3,26 , the identifications of rsRNAs and ysRNAs in a pathophysiological context has only begun to emerge 8,27,28 and has not been studied in AD. The dynamic expression of these non-canonical small RNAs suggests the possibility of unidentified biological functions that warrant further investigation 29,30 , particularly in relation to several risk factor genes that have been identified for AD in the last few decades.…”
Section: Discussionmentioning
confidence: 99%
“…The miRNAs, PIWI-interacting RNAs, long noncoding RNAs (lncRNAs), small nuclear RNAs, transfer RNAs, and circular RNAs are different families of mentioned noncoding RNAs. Among these, lncRNA and miRNA families are clinically significant because of their gene regulatory functions (Ayers & Scerri, 2018). miRNAs are small, 18-23 nucleotide, single-stranded, and nonprotein coding RNAs primarily detected in the nematode Caenorhabditis elegans, then characterized in plants and animals ( Figure 1; Hong, Li, & Su, 2017;G.…”
Section: Microrna Biogenesis and Expressionmentioning
confidence: 99%
“…3′-UTR and lowers the level of this protein (Cheng et al, 2013). According to previous studies, overexpression of miRNA-146a has been observed in the majority of affected areas of AD brains like the hippocampus and temporal cortex (Ayers & Scerri, 2018). Recent miRNA is a regulator of inflammatory responses (Rusca & Monticelli, 2011) and an association has been shown between single nucleotide polymorphisms (SNPs) of this miRNA and risk of AD in the future along with cognitive impairment of AD sufferers (L. Cui et al, 2014).…”
Section: Dementia and Mirna Modificationsmentioning
confidence: 99%
See 1 more Smart Citation